2017
DOI: 10.2147/tcrm.s121812
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid cancer in a patient with Lynch syndrome – case report and literature review

Abstract: Lynch syndrome describes a familial cancer syndrome comprising germline mutations in one of four DNA mismatch repair genes, MLH1, MSH2, MSH6, and PMS2 and is characterized by colorectal, endometrial, and other epithelial malignancies. Thyroid cancer is not usually considered to be part of the constellation of Lynch syndrome cancers nor have Lynch syndrome tumor gene mutations been reported in thyroid malignancies. This study reports a woman with Lynch syndrome (colonic cancer and a DNA mismatch repair mutation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 9 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…We revealed gene and signaling components responsible for PTC manifestation. Lynch syndrome describing a familial cancer syndrome with four DNA mismatch repair genes mutations was found to be associated with PTC [ 74 ]. A high risk of familial adenomatous polyposis (FAP) was found in PTC patients [ 75 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We revealed gene and signaling components responsible for PTC manifestation. Lynch syndrome describing a familial cancer syndrome with four DNA mismatch repair genes mutations was found to be associated with PTC [ 74 ]. A high risk of familial adenomatous polyposis (FAP) was found in PTC patients [ 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…MiR-125b targets a number of genes such as components of signaling cascades and transcriptional factors [ 10 ]. Most of them are universal and highlight the variety of oncogenic processes: cell motility [ 66 , 67 , 68 , 69 , 70 , 71 ], epigenetic regulation [ 69 ] as well as metabolic reprogramming [ 72 , 76 ], viruses [ 70 ], immune response [ 73 ] and familial genetic disorders [ 74 , 75 ]. It was again mentioned that the FOXo signaling cascade participation in PTC oncogenesis as well as in autophagy initiation [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, the genetic basis for FNMTC susceptibility remains largely unknown ( 7 12 ), and FNMTC is not a typical part of the known LS spectrum of tumors. However, previous studies have presented TC as a rare LS-associated cancer in carriers of germline MMR gene mutations ( 51 ) and a handful of case reports document ATC and undifferentiated thyroid cancers ( 35 , 52 ) and PTC in LS patients ( 53 , 54 ), either with or without MSI in the analyzed tumors. However, none of the abovementioned studies have presented FNMTC as a part of the LS comorbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, there are just a few reports of aDTC in the context of MPMN 50–54 and there is no definitive published clinical evidence supporting the use of MKIs in patients with MPMNs and aDTC. The usefulness of MKIs in patients with MPMNs (including DTC) has been described in some patients though, with comparable results to those in a non‐MPMN context 53,55–58 .…”
Section: Treatment Recommendationsmentioning
confidence: 99%
“…Additionally, other non-registrational studies have shown the potential efficacy of MKIs alone or given with other drugs in other advanced cancers, thus increasing their potential usefulness in scenarios associated with DTC and MPMN. 48,49 Nowadays, there are just a few reports of aDTC in the context of MPMN [50][51][52][53][54] and there is no definitive published clinical evidence supporting the use of MKIs in patients with MPMNs and aDTC. The usefulness of MKIs in patients with MPMNs (including DTC) has been described in some patients though, with comparable results to those in a non-MPMN context.…”
mentioning
confidence: 99%